Conflict Analysis of PT Emas Mineral Murni in Nagan Raya and Central Aceh Regency - Putra, Dharma Kelana; Astuti, Wahyu Wiji; Assalam, Muhammad Hafidz (Society, 2020)
This research describes how the mining conflicts in Nagan Raya and Central Aceh Regency between the local community and PT Emas Mineral Murni (PT EMM). This research uses a descriptive qualitative method with a literature study as a data collection technique by searching literature through online news pages on the internet using the search keyword “Aceh Conflict PT EMM”. Content analysis uses Occam’s razor logical principle to read and interpret data to explain a complete picture of the conflict situation without involving unnecessary assumptions. This research found many stakeholders involved in the conflict aside from the local community and PT EMM. Besides, the conflict is focused not only on competition to seize natural resources but also on overlapping legal authority. Low interaction between stakeholders causes conflict to grow and develop. The conflict’s final result is a resolution in the form of a petition signed by the Acting Governor. He stated that he would sue PT EMM with a guarantee of resigning from the position if he cannot realize Acehnese students’ aspirations.